Prevalence of Commorbid Lung Tuberculosis Diabetes Mellitus in Sultan Syarif Mohamad Alkadrie Pontianak Hospital in 2019 - Ardhi, Terence; Fitriangga, Agus; Putri, Eka Ardiani (Faculty of Medicine, Universitas Andalas, 2024)
Pulmonary tuberculosis (TB) can be made worse by a history of Diabetes Mellitus (DM), which can increase the risk of failure treatment, relapse, and longer duration of treatment. Â Objective: To find out the prevalence of Pulmonary TB comorbid DM at Sultan Syarif Mohamad Alkadrie General Hospital Pontianak. Methods: This research was a descriptive observational study with a cross-sectional design. The population in this study were all patients diagnosed with pulmonary tuberculosis at the Sultan Syarif Mohamad Alkadrie Hospital Pontianak from 1 January to December 31st, 2019. Data collection was carried out by taking secondary data on patients diagnosed with pulmonary TB with a history of DM in outpatient and inpatient installations at Sultan Syarif Mohamad Alkadrie General Hospital Pontianak.Results: There were 1311 pulmonary TB patients in Sultan Syarif Mohamad Alkadrie General Hospital Pontianak in 2019; pulmonary TB patients with a history of DM as many as 98 patients obtained from 73 outpatient installations and inpatients hospitalized as many as 25 patients. The results showed that the prevalence of pulmonary TB comorbid DM was 7.47%. Conclusion: The prevalence of pulmonary TB comorbid DM in RSUD Sultan Syarif Mohamad Alkadrie Pontianak is relatively low.Keywords: Â ages, diabetes Â mellitus, pulmonary TB